Association Between Pelvic Floor Muscle Strength and Sexual Function in Postmenopausal Women - Omodei, Michelle Sako [UNESP]; Marques Gomes Delmanto, Lucia Regina [UNESP]; Carvalho-Pessoa, Eduardo [UNESP]; Schmitt, Eneida Boteon [UNESP]; Nahas, Georgia Petri [UNESP]; Petri Nahas, Eliana Aguiar [UNESP] (Oxford University Press (OUP), 2019)
Introduction: Although pelvic floor muscle (PFM) weakness can be associated with pelvic floor dysfunctions, knowledge about the relationship with sexual dysfunction is limited. Aim: The aim of this study was to evaluate the association between PFM strength and sexual function in postmenopausal women. Methods: An analytical cross-sectional study was conducted on 226 sexually active heterosexual women aged 45−65 years with amenorrhea >12 months and without pelvic floor disorders. The Female Sexual Function Index (FSFI) was used for the evaluation of sexual function (total score ≤26.5 indicating sexual dysfunction). PFM strength was assessed by bidigital vaginal palpation using the modified Oxford scale (score 0−5) and was categorized into nonfunctional (scores 0−1, without contraction) and functional (scores 2−5, with contraction). Three-dimensional transperineal ultrasound was used to evaluate total urogenital hiatus area, transverse and anteroposterior diameters, and levator ani muscle thickness. Main Outcome Measure: The main outcome measure was to determine the relationship between sexual dysfunction and PFM strength. Results: The participants were classified as functional PFM (n = 143) and nonfunctional PFM (n = 83). There were no differences between groups in clinical and anthropometric parameters. A higher percentage of menopausal hormone therapy users was observed in the group with functional PFM (39.2%) compared to the nonfunctional group (24.1%; P = .043). Women classified as functional PFM exhibited greater levator ani muscle thickness than those classified as nonfunctional (P = .049). Women with nonfunctional PFM had poorer sexual function in the desire (P = .005), arousal (P = .001), and orgasm (P = 0.006) domains and in total FSFI score (P = .006) compared to the functional group. There was a weak positive correlation of PFM strength with the desire (r = 0.35; P = .0003), arousal (r = 0.21; P = .013), and orgasm (r = 0.23; P = .033) domains and with total FSFI score (r = 0.28; P = .004). Ultrasonographic levator ani muscle thickness showed a weak positive correlation with PFM strength (r = 0.21; P = .046) and with the arousal domain (r = 0.23; P = .044). Risk analysis adjusted for age, time since menopause, parity, and body mass index showed a lower risk of sexual dysfunction in menopausal hormone therapy users (odds ratio = 0.26; 95% CI 0.11−0.60; P = .002) and in women with greater levator ani muscle thickness (odds ratio = 0.85; 95% CI 0.73−0.98; P = .025). Clinical Implications: The maintenance of PFM strength in the climacteric period is an important factor in postmenopausal women's sexual function. Strength & Limitations: The main strength of the study is that, to our knowledge, this is the first study that evaluated the correlation of PFM strength and 3D transperineal ultrasound with different domains of sexual function in postmenopausal women. The main limitation is the cross-sectional design does not permit to establish a cause-effect relationship. Conclusion: Postmenopausal women with PFM dysfunction have poorer sexual function than women with functional PFM. Omodei MS, Marques Gomes Delmanto LR, Carvalho-Pessoa E, et al. Association Between Pelvic Floor Muscle Strength and Sexual Function in Postmenopausal Women. J Sex Med 2019;16:1938–1946.
Keywords: Menopause; Pelvic Floor Muscle; Sexual Function; Three-Dimensional Transperineal Ultrasound